Ganoderic Acid A Metabolites and Their Metabolic Kinetics - Cao, Fang-Rui; Feng, Li; Ye, Lin-Hu; Wang, Li-Sha; Xiao, Bing-Xin; Tao, Xue; Chang, Qi (Frontiers in Pharmacology, 2017)
Ganoderic acid A (GAA), a representative active triterpenoid from Ganoderma lucidum, has been reported to exhibit antinociceptive, antioxidative, cytotoxic, hepatoprotective and anticancer activities. The present study aims 1) to identify GAA metabolites, in vivo by analyzing the bile, plasma and urine after intravenous administration to rats (20 mg/kg), and in vitro by incubating with rat liver microsomes (RLMs) and human liver microsomes (HLMs); 2) to investigate the metabolic kinetics of main GAA metabolites. Using HPLC-DAD-MS/MS techniques, a total of 37 metabolites were tentatively characterized from in vivo samples based on their fragmentation behaviors. The metabolites detected in in vitro samples were similar to those found in vivo. GAA underwent extensive phase I and II metabolism. The main metabolic soft spots of GAA were 3, 7, 11, 15, 23-carbonyl groups (or hydroxyl groups) and 12, 20, 28 (29)-carbon atoms. Ganoderic acid C2 (GAC2) and 7β,15-dihydroxy-3,11,23-trioxo-lanost-26-oic acid were two main reduction metabolites of GAA, and their kinetics followed classical hyperbolic kinetics. The specific isoenzyme responsible for the biotransformation of the two metabolites in RLMs and HLMs was CYP3A. This is the first report on the comprehensive metabolism of GAA, as well as the metabolic kinetics of its main metabolites.